2010
DOI: 10.1167/iovs.09-3431
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Component Growth Curves among Singaporean Children with Different Refractive Error Status

Abstract: In young Asian children, the axial length and vitreous chamber depth increased, but the elongation slowed with age. There was a U-shaped growth curve for lens thickness and an inverted U-shaped curve for anterior chamber depth. The findings of early lens thinning followed by thickening suggest a two-phase growth of the lens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
126
1
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(149 citation statements)
references
References 23 publications
20
126
1
2
Order By: Relevance
“…As a matter of fact, although an emmetropic human eye is expected to grow by less than 3 mm from the ages of 3 to 21 years, 12 larger axial length changes may occur in myopic or pseudophakic children's eyes. [13][14][15] In any event, axial length growth would still likely be <1.0 mm over the course of 3 to 4 years; the average RNFL decline of 2.2 μm attributable an axial length growth of 1.0 mm would still fall within the variance of 9.3 μm 2 for this variable in the present study and other adult published studies. 4 In a clinical setting, children who have mild glaucoma or advanced (largely stable) glaucoma showed high reproducibility for OCT measurements of total macular volume and 16 we found that in children OCT measurements were reproducible for those with a history of elevated IOP.…”
supporting
confidence: 52%
“…As a matter of fact, although an emmetropic human eye is expected to grow by less than 3 mm from the ages of 3 to 21 years, 12 larger axial length changes may occur in myopic or pseudophakic children's eyes. [13][14][15] In any event, axial length growth would still likely be <1.0 mm over the course of 3 to 4 years; the average RNFL decline of 2.2 μm attributable an axial length growth of 1.0 mm would still fall within the variance of 9.3 μm 2 for this variable in the present study and other adult published studies. 4 In a clinical setting, children who have mild glaucoma or advanced (largely stable) glaucoma showed high reproducibility for OCT measurements of total macular volume and 16 we found that in children OCT measurements were reproducible for those with a history of elevated IOP.…”
supporting
confidence: 52%
“…Axial length elongation slowed with age in all children regardless of the type of refractive error, and the depth of the anterior chamber deepened by 9 or 10 years and then became shallower by age 12 [19]. The longest axial lengths and deepest anterior chambers were seen in those with myopia.…”
Section: Eyeball Growth and Increased Axial Lengthmentioning
confidence: 88%
“…In general, eyeball growth is faster in younger children and slows with age [9,19,20]. A MRI eye study of fetuses and children aged 0-13 years shows a rapid eyeball growth curve in utero and from birth to 18 months [20].…”
Section: Structural Development Of the Eyementioning
confidence: 99%
“…Não houve alteração da refração em 6 olhos (55%), que mostraram diferença da refração prévia à final igual ou menor a 0,25 D. Três olhos cresceram sem ter aumento da refração (27%). Dados da literatura mostram que esta variação no crescimento dos olhos portadores de alta miopia foi diferente da encontrada em emétropes na mesma faixa etária escolar (3,24,25) , onde o crescimento não se mostrou significativo. Houve perda de dados no seguimento do estudo, de pacientes que compareciam à primeira consulta e não tinham interesse em dar seguimento, apesar de esclarecimento prévio.…”
Section: Discussionunclassified
“…Houve perda de dados no seguimento do estudo, de pacientes que compareciam à primeira consulta e não tinham interesse em dar seguimento, apesar de esclarecimento prévio. Entretanto, isso parece não invalidar o estudo, uma vez que se obteve todos os dados prévios e finais no período estudado, e os achados obtidos sobre o crescimento do globo ocular são pertinentes com os da literatura (24,25) . A taxa de crescimento ocular é mais significativa nos primeiros 50 meses de vida (2) e posteriormente, no estirão puberal, apresentando variações relacionadas à altura e ao peso do indivíduo.…”
Section: Discussionunclassified